Is the major capsid protein of iridoviruses a suitable target for the study of viral evolution? - Tidona, Christian; Schnitzler, Paul; Kehm, Roland; Darai, Gholamreza (Virus genes, 1998)
Iridoviruses are large cytoplasmic DNA viruses that are specific for different insect or vertebrate hosts. The major structural component of the non-enveloped icosahedral virus particles is the major capsid protein (MCP) which appears to be highly conserved among members of the family Iridoviridae, Phycodnaviridae, and African swine fever virus. The amino acid sequences of the known MCPs were used in comparative analyses to elucidate the phylogenic relationships between different cytoplasmic DNA viruses including three insect iridoviruses (Tipula iridescent virus, Simulium iridescent virus, Chilo iridescent virus), seven vertebrate iridoviruses isolated either from fish (lymphocystis disease virus, rainbow trout virus, European catfish virus, doctor fish virus), amphibians (frog virus 3), or reptiles (turtle virus 3, turtle virus 5), one member of the family Phycodnaviridae (Paramecium bursaria Chlorella virus type 1), and African swine fever virus. These analyses revealed that the amino acid sequence of the MCP is a suitable target for the study of viral evolution since it contains highly conserved domains, but is sufficiently diverse to distinguish closely related iridovirus isolates. Furthermore the results suggest that a substantial revision of the taxonomy of iridoviruses based on molecular phylogeny is required.
Gesehen am 29.08.2024